Health science libraries in the United States: I. Overview of the post-World War II years. - Crawford, S (1983)
Data from three surveys of health sciences libraries in the United States (1969, 1973, and 1979) were analyzed within the context of scientific, technological, and sociopolitical developments. Findings included decrease in the number of separately administered libraries, growth of some, decline or discontinuation of others, and geographic movement. Overall, the aggregate resources are increasing, as is cooperation among libraries.